Laparoscopic cholecystectomy under spinal-epidural anesthesia versus general anaesthesia: a prospective randomized study - Ahmed, Kawser; Hel Baki, M. Abdullah; Begum, Monira; Barman, Nirmal K.; Hossein, M. Monwar; Islam, M. Shafiqul; Shil, Shiladitya (International Journal of Research in Medical Sciences, 2024)
Background: The choice between spinal-epidural anesthesia and general anesthesia for laparoscopic cholecystectomy depends on various factors, including patient characteristics, surgical team expertise, and institutional guidelines. While both techniques have their advantages and disadvantages, spinal-epidural anesthesia offers an alternative to general anesthesia, potentially reducing complications and improving patient outcomes. Objective of the study was to compare spinal anesthesia with the gold standard general anesthesia for elective laparoscopic cholecystectomy in healthy patients. Methods: This study was conducted at Sheikh Hasina Medical College, Hobiganj, Bangladesh. In this prospective comparative study, we enrolled one hundred patients diagnosed with symptomatic gallstone disease and classified as American Society of Anesthesiologists (ASA) status I or II. These patients were subjected to randomization, with fifty of them assigned to undergo laparoscopic cholecystectomy under spinal anesthesia, while the remaining fifty received general anesthesia. Subsequently, we conducted a comprehensive assessment, comparing various intraoperative parameters, postoperative pain levels, incidence of complications, recovery rates, and patient satisfaction during the follow-up period, with the aim of evaluating the differences between these two anesthesia methods. Results: All the procedures were completed by the allocated method of anesthesia, as there were no conversions from spinal to general anesthesia. Pain was significantly less at 4 hours (p<0.001), 8 hours (p<0.001), 12 hours (p<0.001), and 24 hours (p=0.02) after the procedure for the spinal anesthesia group compared with those who received general anesthesia. There was no difference between the 2 groups regarding complications, hospital stay, recovery, or degree of satisfaction at follow-up. Conclusions: Spinal anesthesia is adequate and safe for laparoscopic cholecystectomy in otherwise healthy patients and offers better postoperative pain control than general anesthesia without limiting recovery.